The Influence of Principal Leadership and Work Discipline Through Work Motivation on the Performance of Elementary School Teachers (Educational Management, 2022)
The purpose of this study is to analyze the direct or indirect influence of the principal's leadership and work discipline through work motivation on teacher performance. Education in schools can not be separated from the role of teachers, where teachers in education are needed during the teaching and learning process and distribute information that happens in school. Teachers are the most important human resources capable of assisting students in gaining knowledge, and insight, and forming good personalities at school. Teachers play a big role and influence in realizing educational goals. This research is quantitative by using path analysis as the data analysis using SPSS and Sobel Test Calculator. The sample of this study was 67 students, consisting of 18 elementary schools throughout the Kadipaten District, and taken using proportionated cluster random sampling. The research instrument used a questionnaire. The results showed that Direct leadership, work discipline, and work motivation affect teacher performance. While the indirect effect of motivation is able to mediate the influence of leadership and work discipline on teacher performance. The conclusion is there is a direct influence of the principal's leadership and work discipline on teacher performance, as well as indirect work motivation, which can mediate the influence of the independent variable to the dependent.